The theory of exciton states in quasi-zero-dimensional semiconductor systems - Pokutnyi, S.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
For a semiconductor quantum dot (QD), the contributions made to the exciton energy spectrum by the electron and hole kinetic energies, the energy of Coulomb interaction between them, and the energy of their polarization interaction with the spherical interface between the QD and the dielectric medium have been analyzed.